The Influence of Social Media Marketing Activities on Continued Usage Intentions and Brand Loyalty: The Mediating Role of Brand Experience, Brand Awareness, and Satisfaction (A Study on Wardah Cosmetics in Indonesia) - Munandar, Shella Stefani; Wahyudi, Lilik (Dinasti International Journal of Economics, Finance & Accounting, 2026)
This study investigates the influence of Social Media Marketing Activities on continued usage intention and brand loyalty through the mediating roles of brand experience, brand awareness, and satisfaction among Wardah consumers in Indonesia. Using a quantitative survey approach with purposive sampling, data were collected from 350 active social media users who had experience using Wardah products. The data were analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS version 4. The results show that Social Media Marketing Activities have a significant effect on all dimensions of brand experience, including sensory, affective, behavioral, and intellectual aspects, as well as on brand awareness and satisfaction. Intellectual brand experience was found to be the strongest predictor of continued usage intention, while brand awareness and satisfaction act as important mediators linking marketing efforts to consumer behavior. The model explains 83.9% of the variance in continued usage intention and 60.5% in brand loyalty, confirming the relevance of the Stimulus Organism Response framework. Overall, this research enriches theoretical understanding and provides practical guidance for cosmetic brands to design interactive, consistent, and personalized social media strategies that enhance satisfaction, engagement, and long-term loyalty in the digital marketplace.